Ramuan Tradisional Nusantara Abad Ke-16 Naskah Tetamba Cirebon - Hidayani, Fika (IAIN Syekh Nurjati Cirebon, 2023)
The use of traditional herbs, which have been utilized by ancestors for centuries, serve as a potential alternative supplement for treating diseases in modern times. This study centers on the utilization of traditional herbs documented in ancient manuscripts. The source utilized in this study is the 16th century manuscript Kitab Tetamba Cirebon, written in Javanese and Arabic, and collected by Bambang Irianto, a customary holder of Kacirebonan Palace. The content analysis method was used in this study. The study findings indicate that 100 different types of herbal plants can be used to treat 83 curable diseases through methods such as pounding, heating, drinking and applying. The Kitab Tetamba Cirebon manuscript illustrates that ancestral knowledge and practices can serve as an alternative treatment approach for present-day maladies.